Evaluation of HIV Reporting Form in Sana'a City, Yemen, 2016. (May 2019) - Abdulrazzak, Mahmoud Hassan; Alsahybi, Abdul Hamid; Assabri, Ali; Khader, Yousef
Yemen has witnessed a significant rise in AIDS-related deaths because of very poor access to antiretroviral treatment and because of the current war situation. This study aimed to assess the attributes of human immunodeficiency virus (HIV) reporting form, including usefulness, simplicity, flexibility, and acceptability, which is used for reporting HIV cases in Sana'a, Yemen. A descriptive cross-sectional study was conducted among 311 physicians from public and private health facilities in Sana'a city. Physicians were interviewed using a structured questionnaire to assess the form's attributes. The mean score was calculated for each attribute and converted to percentages which were interpreted as very poor, poor, average, good, and excellent. The usefulness overall score was 76%, indicating average usefulness. Of the total participants, 283 (91%) and 304 (97.7%) stated that the form is clear and easy to fill, respectively. More than two-thirds (68.5%) of physicians stated that the form ensures the privacy of the customer's identity. The simplicity attribute score was 74.5%, indicating average simplicity. The overall flexibility was 69.2%, indicating average flexibility. A total of 175 (56%) physicians indicated that they are completely satisfied with the reporting form. The acceptability score was 75.2%, indicating that the HIV/AIDS reporting form of HIV is average in acceptability. The HIV/AIDS reporting form in Yemen was scored average in usefulness, simplicity, flexibility, and acceptability. Training health workers on using the reporting form would improve the performance of HIV/AIDS reporting. Moreover, the reporting form could be adapted to be integrated with other surveillance such as tuberculosis surveillance.